EFFECT OF VITAMIN E (α-TOCOPHEROL) ADMINISTRATION ON SPERM MOTILITY AND MORPHOLOGY OF SPRAGUE DAWLEY STRAIN RATS AFTER CISPLATIN TREATMENT - Aditya, Dimas Visa; Djojodimedjo, Tarmono; Soebadi, Doddy M (Indonesian Urological Association, 2019)
Objective: To evaluate the protective effects of vitamin E α-tocopherol isomer against the toxicity of cisplatin on sperm motility and morphology in Sprague Dawley rats. Material & Methods: Twenty-four rats were grouped into four groups (n=6). The control group (CN) was injected with normal saline, second group (CP) was injected with cisplatin, the third group (P1) was injected with cisplatin and vitamin E 50 mg/kgBW for 7 weeks P.O, the fourth group (P2) was injected with cisplatin and vitamin E 200 mg/kgBW for 7 weeks P.O. Vitamin E was given from 3 weeks before cisplatin injection and 4 weeks following cisplatin injection. At 7th week, all the samples were undergoing bilateral orchidectomy. Vitamin E that being used in this study was α-tocopherol isomer. Results: Cisplatin decreased motility and morphology of spermatozoa significantly against controls. Vitamin E 50 mg/kgBW and 200 mg/kgBW significantly increased motility of spermatozoa (p<0.05) compared to those in the cisplatin group only. Vitamin E 50 mg/kgBW, and 200 mg/kgBW did not have a significant difference in spermatozoa motility compare to control groups. Vitamin E 50 mg/kgBW and 200 mg/kgBW could increase the spermatozoa morphology significantly compare to those cisplatin only group. Vitamin E 50 mg/kgBW, and 200 mg/kgBW did not have a significant difference in spermatozoa morphology compared to control groups. Conclusion: α-tocopherol 50 mg/kgBW and 200 mg/kgBW provided a same protective effect against spermatozoa damage especially in motility and morphology aspect due to cisplatin exposure. Therefore, in this study it was more recommended to use α-tocopherol in 50 mg/kgBW dose than 200 mg/kgBW.